Protective role of virgin coconut oil on potent biochemical biomarkers in Wistar rat model of comorbid depression - Kulyadi, Chitra Pai; Noojibail, Anupama; Kumar, Nayanatara Arun; Kollampare, Sowndarya; Dass, Prameela Manoor (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: Chronic stress arises from stressful situations in day-to-day life that are ignored or managed incorrectly. Long-term stress can have negative effects, especially when it plays a role in the development of neurological illnesses. Severe stress can also negatively impact emotional well-being. Virgin coconut oil (VCO) has numerous health advantages. The aim of this study was to assess how VCO affected the biochemical and behavioral characteristics of Wistar albino rats exposed to chronic, unpredictable stress. Materials and Methods: Healthy Wistar albino rats (150–200 gm) were split into two groups: experimental group and control group. Based on stress exposure and treatment with VCO and antidepressants, they were further divided into various subgroups. A chronic, unpredictable stress procedure was given for 21 days. After the experimental procedure, the rats were anesthetized, and through a cardiac puncture, blood was collected. The liver and brain were dissected to estimate different biochemical markers. Results: VCO proved to be a protective agent against chronic, unpredictable stress-induced changes in the biochemical parameters, hepatic enzyme activity, lipid profile, oxidative stress, and cognition. Conclusion: VCO might be helpful as an effective natural treatment that can be utilized to effectively combat chronic, unpredictable stress-induced changes in brain and liver tissue. Adv. Vet. Anim. Res., 11(2): 449-454, June 2024 http://doi.org/10.5455/javar.2024.k794